PENGARUH PUPUK ORGANIK GEBAGRO 77 TERHADAP PERTUMBUHAN KAPULAGA (AMOMUM COMPACTUM) DI DESA BOTOHILI SILAMBO - Herlina Halawa (Universitas Nias Raya, 2023)
Lack of understanding of farmers in Botohili Silambo Village in utilizing gebagro 77 organic fertilizer as fertilizer, especially on cardamom plants. People still use inorganic (chemical) fertilizers, thereby reducing soil quality. This study aims to determine the effect of organic fertilizer gebagro 77 on the growth of cardamom (Amomum compatum). This type of research is quantitative with a pure experimental method (True Experiment) with a completely randomized design (CRD). The population of this study was 20 polybags of cardamom and the sample of this study was cardamom with five treatments and four replications. The treatments applied were P0 (without giving gebagro 77 organic fertilizer) P1 (5 grams), P2 (10 grams), P3 (15 grams), and P4 (20 grams). The data of this study were analyzed using the Kolmogorov-Smirnov test for normality test, homogeneity test, hypothesis testing using the SPSS (Statistical Product and Service Solution) application version 20. It is known that Fcount 3.141 and asymp 0.046, with Ftable 2.90 then Fcount 3.141 > Ftable 2.90 and Asymp value 0.046 < 0.05. It shows that the height of cardamom stems is better than those that do not use gebagro 77 fertilizer. While it is known that Fcount 3.352 and Asymp 0.038, with Ftable 2.90 then Fcount 3.352 > Ftable 0.038 and Asymp value 0.038 < 0.05. It shows that the number of cardamom plant leaves is more than those that do not use gebagro 77 fertilizer. From the results of the analysis, the average use of gebagro 77 organic fertilizers has a better stem height and number of leaves compared to those who do not use gebagro 77 organic fertilizers. The suggestion offered by researchers is that the use of gebagro 77 organic fertilizers should be increased to reduce use of inorganic fertilizers and utilize existing natural resources.